Activation of ATF3/AP-1 signaling pathway is required for P2X3-induced endometriosis pain. Issue 5 (18th April 2020) - Ding, Shaojie; Yu, Qin; Wang, Jianzhang; Zhu, Libo; Li, Tiantian; Guo, Xinyue; Zhang, Xinmei
Abstract: STUDY QUESTION: Does P2X ligand-gated ion channel 3 (P2X3) play a role in endometriosis pain? SUMMARY ANSWER: Upregulation of P2X3 in dorsal root ganglia (DRG) tissues via the activating transcription factor 3 (ATF3)/activator protein (AP)-1 pathway contributed to endometriosis-associated hyperalgesia, which could be attenuated by the chitosan oligosaccharide stearic acid (CSOSA)/liposomes (LPs)/SP600125 delivery system. WHAT IS KNOWN ALREADY: Infiltrating nerve fibers and elevated nociceptors in endometriotic lesions are associated with endometriosis pain. P2X3 has been demonstrated to play an important role in neuropathic pain. STUDY DESIGN, SIZE, DURATION: A rat model of endometriosis was used to investigate the signaling pathways involved in P2X3-induced pain. PARTICIPANTS/MATERIALS, SETTING, METHODS: Degrees of hyperalgesia, endogenous adenosine 5′-triphosphate (ATP) contents and P2X3 expression levels in endometriotic lesions and DRG tissues were detected in a rat model of endometriosis. The expression levels of ATF3 and P2X3 were measured using qRT-PCR, western blot analysis and immunofluorescence analysis after adenosine 5′-diphosphate (ADP) exposure in DRG cells. Plasmids encoding ATF3 and its siRNA were used to investigate the role of ATF3 on ADP-induced P2X3 upregulation. The activity of ATF binding to the P2X3 promoter was evaluated by using chromatin immunoprecipitation (CHIP) and luciferase assays. SP600125, an inhibitor of c-JUN N-terminal kinase, was wrapped in CSOSA/LPs delivery system and its inhibitory effects on ADP-induced upregulation of P2X3 in DRG cells and endometriosis-induced hyperalgesia in rats were tested. MAIN RESULTS AND THE ROLE OF CHANCE: The concentrations of endogenous ATP and expression levels of P2X3 were significantly increased in both endometriotic lesions and DRG tissues in endometriosis rat models and were found to be positively correlated with the severity of hyperalgesia. In DRG cells, P2X3 expression levels were elevated by ADP stimulation, but dramatically inhibited by blocking ATF3 with its siRNA and SP600125. CHIP and luciferase assay showed that ADP increased the binding of ATF3 to the P2X3 promoter, resulting in an increase in P2X3 expression levels. In the CSOSA/LPs/SP600125 delivery system, the drug could be effectively concentrated in endometriotic lesions, and it could alleviate endometriosis-induced hyperalgesia, reduce the size of endometriotic lesions and attenuate upregulated P2X3 expression levels in endometriosis rat models. LARGE SCALE DATA: N/A LIMITATIONS, REASONS FOR CAUTION: Changes in the sensitivity and function of P2X3 caused by endometriosis need to be further investigated. WIDER IMPLICATIONS OF THE FINDINGS: This study indicates that ATP and the P2X3 receptor are involved in endometriosis pain, thus providing a novel therapeutic approach for the treatment of endometriosis pain by targeting the P2X3 receptor. STUDY FUNDING/COMPETING INTEREST(S): This work was funded by National Key R&D Program of China (Grant No. 2017YFC1001202) and National Natural Science Foundation of China (Grant Nos. 81974225, 81671429 and 81471433). There are no competing interests.